Microevolution of Aedes aegypti - Louise, Caroline; Vidal, Paloma Oliveira; Suesdek, Lincoln (PLOS ONE, 2015)
Scientific research into the epidemiology of dengue frequently focuses on the microevolution and dispersion of the mosquito Aedes aegypti. One of the world’s largest urban agglomerations infested by Ae. aegypti is the Brazilian megalopolis of Sao Paulo, where >26,900 cases of dengue were reported until June 2015. Unfortunately, the dynamics of the genetic variability of Ae. aegypti in the Sao Paulo area have not been well studied. To reduce this knowledge gap, we assessed the morphogenetic variability of a population of Ae. aegypti from a densely urbanised neighbourhood of Sao Paulo. We tested if allelic patterns could vary over a short term and if wing shape could be a predictor of the genetic variation. Over a period of 14 months, we examined the variation of genetic (microsatellites loci) and morphological (wing geometry) markers in Ae. aegypti. Polymorphisms were detected, as revealed by the variability of 20 microsatellite loci (115 alleles combined; overall Fst = 0.0358) and 18 wing landmarks (quantitative estimator Qst = 0.4732). These levels of polymorphism are higher than typically expected to an exotic species. Allelic frequencies of the loci changed over time and temporal variation in the wing shape was even more pronounced, permitting high reclassification levels of chronological samples. In spite of the fact that both markers underwent temporal variation, no correlation was detected between their dynamics. We concluded that microevolution was detected despite the short observational period, but the intensities of change of the markers were discrepant. Wing shape failed from predicting allelic temporal variation. Possibly, natural selection (Qst>Fst) or variance of expressivity of wing phenotype are involved in this discrepancy. Other possibly influential factors on microevolution of Ae. aegypti are worth searching. Additionally, the implications of the rapid evolution and high polymorphism of this mosquito vector on the efficacy of control methods have yet to be investigated.